Thermodynamics of neptunium(V) complexation with sulfate in aqueous solution. (January 2018) - Maiwald, Martin M.; Sittel, Thomas; Fellhauer, David; Skerencak-Frech, Andrej; Panak, Petra J.
Graphical abstract: Highlights: Complexation of NpO2 + with SO4 2− is studied as a function of T and Im by UV/Vis/NIR. log β 0 (T), Δr H 0 m, Δr S 0 m is determined at IUPAC reference state. The ionic strength dependence is described by the SIT and εj, k (T) is calculated. Abstract: The complexation of NpO2 + with sulfate is studied in aqueous solution using absorption spectroscopy. The total ligand concentration (Na2 SO4 ), ionic strength (NaClO4 ), and temperature (T = 20–85 °C) is varied, yielding detailed information on the thermodynamics of the complexation reaction. A single complex species (NpO2 (SO4 ) − ) is identified by peak deconvolution of the absorption spectra. The molar fraction of the complex species increases with increasing temperature. The conditional stability constants log β′1 (T) are calculated and extrapolated to zero ionic strength for each temperature condition with the specific ion interaction theory (SIT). The determined log β 0 1 (T) values increase by approximately one logarithmic unit in the studied temperature range. Furthermore, the log β 0 1 (T) values are linearly correlated with the reciprocal temperature. Thus, fitting the data according to the integrated Van't Hoff equation yields the standard reaction enthalpy (Δr H 0 m ) and entropy (Δr S 0 m ) of the formation of the NpO2 (SO4 ) − complex. The results show an endothermic reaction which is solely driven by the reaction entropy. In addition, the binary SIT ion-ion interaction coefficient ε(Na +, NpO2 (SO4 ) − ) of the complex species is determined.